Self-managed occupational therapy and physiotherapy for adults receiving inpatient rehabilitation ('My Therapy'): protocol for a stepped-wedge cluster randomised trial - Natasha K. Brusco; Christina L. Ekegren; Nicholas F. Taylor; Keith D. Hill; Annemarie L. Lee; Lisa Somerville; Natasha A. Lannin; Derick Wade; Rania Abdelmotaleb; Libby Callaway; Sara L. Whittaker; Meg E. Morris (BMC, 2021)
Abstract Background Ensuring patients receive an effective dose of therapeutic exercises and activities is a significant challenge for inpatient rehabilitation. My Therapy is a self-management program which encourages independent practice of occupational therapy and physiotherapy exercises and activities, outside of supervised therapy sessions. Methods This implementation trial aims to determine both the clinical effectiveness of My Therapy on the outcomes of function and health-related quality of life, and cost-effectiveness per minimal clinically important difference (MCID) in functional independence achieved and per quality adjusted life year (QALY) gained, compared to usual care. Using a stepped-wedge cluster randomised design, My Therapy will be implemented across eight rehabilitation wards (inpatient and home-based) within two public and two private Australian health networks, over 54-weeks. We will include 2,160 patients aged 18 + years receiving rehabilitation for any diagnosis. Each ward will transition from the usual care condition (control group receiving usual care) to the experimental condition (intervention group receiving My Therapy in addition to usual care) sequentially at six-week intervals. The primary clinical outcome is achievement of a MCID in the Functional Independence Measure (FIM™) at discharge. Secondary outcomes include improvement in quality of life (EQ-5D-5L) at discharge, length of stay, 30-day re-admissions, discharge accommodation, follow-up rehabilitation services and adverse events (falls). The economic outcomes are the cost-effectiveness per MCID in functional independence (FIM™) achieved and per QALY gained, for My Therapy compared to usual care, from a health-care sector perspective. Cost of implementation will also be reported. Clinical outcomes will be analysed via mixed-effects linear or logistic regression models, and economic outcomes will be analysed via incremental cost-effectiveness ratios. Discussion The My Therapy implementation trial will determine the effect of adding self-management within inpatient rehabilitation care. The results may influence health service models of rehabilitation including recommendations for systemic change to the inpatient rehabilitation model of care to include self-management. Findings have the potential to improve patient function and quality of life, and the ability to participate in self-management. Potential health service benefits include reduced hospital length of stay, improved access to rehabilitation and reduced health service costs. Trial registration This study was prospectively registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12621000313831; registered 22/03/2021, http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=380828&isReview=true ).